2008
DOI: 10.1002/cm.20329
|View full text |Cite
|
Sign up to set email alerts
|

Functional implications of membrane modification with semenogelins for inhibition of sperm motility in humans

Abstract: Semenogelin I and II (Sgs) are the major component of human semen coagulum. The protein is rapidly cleaved after ejaculation by a prostate-specific antigen, resulting in liquefaction of the semen coagulum and the progressive release of motile spermatozoa. Sgs inhibit human sperm motility; however, there is currently no information on its effect on the sperm membrane. This study investigated the role of Sgs on human sperm motility through regulation of membrane potential and membrane permeability. Fresh semen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Semenogelin is a protein that mechanically traps spermatozoa and inhibits sperm motility and capacitation [17]. The addition of trypsin, a serine protease, in the seminal extender can precipitate the dissolution of the sperm coagulum [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Semenogelin is a protein that mechanically traps spermatozoa and inhibits sperm motility and capacitation [17]. The addition of trypsin, a serine protease, in the seminal extender can precipitate the dissolution of the sperm coagulum [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Sgs and/or their degradation products may be natural regulators of sperm motility [18,19] and capacitation [20] . Previously, we revealed that the SPMI/Sg content of seminal plasma was negatively correlated with sperm motility in normal subjects [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Such a tendency was not observed in any of the other parameters, including the proportion of SEMG+. Although the precise molecular mechanism underlying the controlling fertilizing capacity of sperm in vivo have not been revealed, the role of SEMGs on sperm were well studied and proved to control motility and capacitation [ 8 , 16 – 18 ]. Moreover, according to our analysis in knockout mice, seminal vesicle secretion 2 (SVS2), an orthologue of SEMGs, is essential for in vivo fertilization [ 13 ].…”
Section: Discussionmentioning
confidence: 99%